Prediction of ionic liquid's heat capacity by means of their in silico principal properties. Issue 42 (12th April 2016) - Paternò, Alessio; Fiorenza, Roberto; Marullo, Salvatore; Musumarra, Giuseppe; Scirè, Salvatore
Abstract : VolSurf+ in silico principal properties of ionic liquids were used to develop a QSPR model providing affordable heat capacity predictions which were experimentally validated. Abstract : The in silico principal properties (PPs) of ionic liquids (ILs), derived by means of the VolSurf+ approach, were used to develop a Partial Least Squares (PLS) model able to find a quantitative correlation among IL descriptors (accounting for both cationic and anionic structural features) and heat capacity values, providing affordable predictions validated by experimental C p measurements for an external set of ILs. In silico predictions allowed the selection of a limited number of structurally different ILs with similar C p values, providing the possibility to select an optimal IL according to efficiency, as well as to environmental and economic sustainability. The present general procedure, using readily available descriptors for above 8000 ILs and adopting an accessible statistical procedure such as PLS, could be extended to other QSPR models.